PENGARUH CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA DI INDUSTRI PERBANKAN PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Hasan Abdur Rohman Lutfi; Iwan Fakhruddin (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
This research was aimed at examining the factors influencing earnings management. The independent variables in this research were institutional ownership, size of commisioner board, independent commissioner, and audit committee. The data of this research were audited financial statement and annual report of the companies obtained from www.idx.co.id. The samples of this research were conventional banking companies listed in Indonesia Stock Exchange 2010-2013. The hypothesis test done in this research was multiple regression analysis.The result of this research showed that institutional ownership did not have negative and significant effect on the earnings management. The size of commissioner board had positive and significant effect on the earnings management. Independent commissioner did not have negative and significant effect on the earnings management. Audit commite did not have negative and significant effect on the earnings management.Keywords : Corporate Governance (Institutional Ownership, Size of Commissioner Board, Independent Commissioner an Audit Committee).